Integrative Analysis of Elicitor-Induced Camptothecin Biosynthesis in Camptotheca acuminata Plantlets Through a Combined Omics Approach - Pu, Xiang; Gao, Hu-Chuan; Wang, Min-Ji; Zhang, Jia-Hua; Shan, Jia-Heng; Chen, Meng-Han; Zhang, Li; Wang, Han-Guang; Wen, An-Xiang; Luo, Ying-Gang; Huang, Qian-Ming (Frontiers in Plant Science, 2022)
Treatments with abiotic elicitors can efficiently induce the accumulation of specialized metabolites in plants. We used a combined omics approach to analyze the elicitation effects of MeJa, AgNO3, and PEG on camptothecin (CPT) biosynthesis in Camptotheca acuminata plantlets. Untargeted analyses revealed that treatments with MeJa, AgNO3, and PEG significantly inhibited the photosynthetic pathway and promoted carbon metabolism and secondary metabolic pathways. The CPT levels increased by 78.6%, 73.3%, and 50.0% in the MeJa, AgNO3, and PEG treatment groups, respectively. Using C. acuminata plantlets after elicitation treatment, we mined and characterized 15 new alkaloids, 25 known CPT analogs and precursors, 9 iridoid biosynthetic precursors, and 15 tryptamine biosynthetic precursors based on their MS/MS fragmentation spectra. Using 32 characterized genes involved in CPT biosynthesis as bait, we mined 12 prioritized CYP450 genes from the 416 CYP450 candidates that had been identified based on co-expression analysis, conserved domain analysis, and their elicitation-associated upregulation patterns. This study provides a comprehensive perspective on CPT biosynthesis in C. acuminata plantlets after abiotic elicitation. The findings enable us to elucidate the previously unexplored CYP450-mediated oxidation steps for CPT biosynthesis.